Regulatory focus and sexual health: Motives for security and pleasure in sexuality are associated with distinct protective behaviors - Rodrigues, D. L. (2021)
We examined if motives for security (i.e., prevention focus) or pleasure (i.e., promotion focus) were uniquely associated with intentions to get tested for STIs and behavioral control over condom use, over and above variables already identified in theoretical models. We conducted an online survey with Portuguese adults (N = 836; Mage = 22.27, SD = 5.14). Overall, 99.4% of the participants knew at least one of eight STIs, but only 25.2% got tested in the last six months. Participants more focused on prevention had condomless sex less frequently, whereas participants more focused on promotion knew more STIs and got tested for more STIs. Furthermore, participants had stronger intentions to get tested for STIs if they got tested for more STIs in the past, were more concerned about STIs, perceived greater susceptibility to STI acquisition, and were more focused on promotion (but not prevention). Participants had greater behavioral control over condom use if they had condomless sex less often and were more focused on prevention (but not promotion). These findings suggest that promotion-focused people are more likely to consider the consequences of having condomless sex. In contrast, prevention-focused people are more likely to take control of their sexual health.